Origins and Ends of the Mind : Philosophical Essays on Psychoanalysis - Brassier, Ray; Kerslake, Christian (Book collections on Project MUSE., 2007)
Psychoanalysis claims that the individual human mind is structured by its childhood relationships with its parents. But the theory of attachment, evolutionary psychology and contemporary philosophy of mind have all recently re-introduced new dimensions of innateness into mental development and pathology. If attachment is an instinct, then what is the psychological status of the child''s relation to the mother? If the mind is in part a product of evolution, then how far down do the inhibitory mechanisms of the mind go? If the mind of the child is shaped by their encounter with a set of prohibit.